2004
DOI: 10.1172/jci200421307
|View full text |Cite
|
Sign up to set email alerts
|

Mature high-affinity immune responses to (pro)insulin anticipate the autoimmune cascade that leads to type 1 diabetes

Abstract: Children at risk for type 1 diabetes can develop early insulin autoantibodies (IAAs). Many, but not all, of these children subsequently develop multiple islet autoantibodies and diabetes. To determine whether disease progression is reflected by autoantibody maturity, IAA affinity was measured by competitive radiobinding assay in first and subsequent IAA-positive samples from children followed from birth in the BABYDIAB cohort. IAA affinity in first positive samples ranged from less than 10 6 l/mol to more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
0
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(180 citation statements)
references
References 33 publications
6
163
0
10
Order By: Relevance
“…Interestingly, GADA binding to the middle and/or C-terminal part of GAD65 could be of high or low affinity, and this was strongly related to the islet autoantibody status. The occurrence of GADA plus IAA and/or IA-2A was predominantly seen in children with high-affinity autoantibodies, confirming previous reports from us and others [25,27,28]. In contrast, GADA binding only to the N-terminal part of GAD65 involved predominantly single low-affinity GADA level (KU/l) GADA C-terminal level (AU) Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, GADA binding to the middle and/or C-terminal part of GAD65 could be of high or low affinity, and this was strongly related to the islet autoantibody status. The occurrence of GADA plus IAA and/or IA-2A was predominantly seen in children with high-affinity autoantibodies, confirming previous reports from us and others [25,27,28]. In contrast, GADA binding only to the N-terminal part of GAD65 involved predominantly single low-affinity GADA level (KU/l) GADA C-terminal level (AU) Fig.…”
Section: Discussionsupporting
confidence: 89%
“…1b). As in findings in IAA-positive first-degree relatives [7], IAA affinity of ≥10 9 l/mol was a discriminatory threshold: 22 (92%) of the 24 children who developed other islet autoantibodies or diabetes had IAA affinities ≥10 9 l/mol, compared with only four (18%) of 22 of the children who did not progress to multiple islet autoantibodies or diabetes (p<0.0001).…”
Section: Resultssupporting
confidence: 54%
“…For early risk assessment, therefore, it would be useful to identify IAA-positive children who will develop other islet autoantibodies. We showed that high IAA affinity and proinsulin reactivity were characteristics of IAA in first-degree relatives who developed further islet autoantibodies and type 1 diabetes [7]. The purpose of this study was to extend these findings to children from the general population.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations